SIIF2008 - Kipli, Nur Aida; Ramakrishnan, Prabha; Maniam, Yuthandy; Abdullah, Norazlin; Jack, Suriani; Abg Samah, Aizimah; Chiew, Fei Ha (Universiti Teknologi MARA, Sarawak, 2009)
UiTM sent 13 teams to participate in the Seoul International Invention Fair 2008 (SIIF08) organized by the Korean Invention Promotion Association from 11-15 December 2008. The contingent brought back 2 gold, 6 silver and 5 bronze prizes. The team made up of Dr. Paul Lau Ngee Kiong and Lau Sie Hoe from UiTM Sarawak with their product "A computer-adaptive multiple-choice assessment for learning (CAAS)" managed to get a silver prize.